Alginate-based hydrogels prepared via ionic gelation: An experimental design approach to predict the crosslinking degree. (September 2019) - Dodero, Andrea; Pianella, Lara; Vicini, Silvia; Alloisio, Marina; Ottonelli, Massimo; Castellano, Maila
Graphical abstract: Highlights: Alginate-based hydrogels prepared by means of agar moulds. Full factorial experimental design applied to build mathematical models. Investigation of hydrogel swelling and mechanical properties. Effective crosslinking degree calculated using a Flory's model. Abstract: Alginate-based hydrogels can be obtained by the simple addition of bivalent ions to aqueous polysaccharide solutions without the use of toxic chemicals; however, the hydrogels prepared by this way result inhomogeneous and irreproducible due to the extremely fast crosslinking reaction. To overcome such limitations, in the present work a novel preparation approach is proposed and optimized; the method is based on the use of agar moulds rich of bivalent ions as diffusing system to modulate the release of Ca 2+, Sr 2+, and Ba 2+ cations in order to guarantee a better control of the crosslinking process. A full factorial experimental design was applied to assess the effects and the mutual interactions of three selected parameters (sodium alginate concentration, crosslinking agent concentration within the agar moulds, crosslinking time) on the gelation process. The swelling and mechanical properties of the prepared hydrogels were investigated both in deionized water and in a saline environment; furthermore, the hydrogels were characterized by means of thermogravimetric analysis and field-emission scanning electron microscopy. The obtained results demonstrated that both the experimental variables and the environmental conditions have a significant influence on the structure and the performances of the resulting hydrogels. In particular, the use of high polymer concentration and crosslinking agent amount leads to strong hydrogels corresponding to a superior crosslinking degree; more in detail, Ba 2+ ions show a great affinity for alginate leading to the hydrogels with the highest mechanical properties. Moreover, the ion-exchange occurring in saline environment seems to strongly reduce the effective crosslinking degree of alginate hydrogels with a consequential loss of mechanical properties and stability. The collected data were finally elaborated through statistical analysis combined with response surface methodology to develop theoretical models successfully able to correlate the crosslinking degree to the experimental conditions, thus opening the way of designing and fabricating alginate-based hydrogels with tailored morphology and mechanical properties.